Konsep dan Pendekatan Wasatiyah dalam Pengeluaran Fatwa: Satu Kajian Awal: The Concept and Approach of Wasatiyyah in Issuing Fatwa: A Premilinary Study - Rosele, Muhammad Ikhlas; Abdul Rahman, Noor Naemah (Online Journal of Research in Islamic Studies, 2019)
Fatwa is one of the important instruments and tools in Islamic law. This is due to fatwa are decided for the individual and the community based on some circumstances and the reality of their environment. But excessive openness and closeness in issuing a fatwa causes problems to the community system in the form of thoughts, affairs and interactions. Therefore, the study aimed to identify the wasatiyyah approach in issuing fatwa in Malaysia with highlighting some of the selected fatwa in Malaysia. The study will be conducted using a qualitative approach in which library data is used in full. It is then analyzed inductively and deductively. Studies have identified several elements in the wasatiyyah approach to issuing fatwa and it is found that the fatwa body in Malaysia considers this approach in solving current issues.